Malnutrition and the Older Adult - Wendy J. Dahl (EDIS)
FSHN10-09, a 3-page illustrated fact sheet by Wendy J. Dahl, answers questions about malnutrition in older adults and provides ways to help older adults meet their nutritional needs. Includes references. Published by the UF Department of Food Science and Human Nutrition, July 2010.